Using Machine Learning to Score Multidimensional Assessments of Students' Skill Levels in Mathematics. - Doungruethai Chitaree; Putcharee Junpeng; Suphachoke Sonsilphong; Keow Ngang Tang (Pertanika Journal of Social Sciences & Humanities, 2024)
This research aims to establish a mathematical skill measurement model to examine seventhgrade students' mathematical skills in two aspects: their understanding of mathematical processes and the concept and structure. The researchers surveyed the mathematical skills of 521 seventh-grade students from the northeastern province of Thailand. Their test results were used to prototype a mathematical skill measurement model using machine learning. It involved a design-based approach that included four stages: a construct map, item design, a Wright Map, and outcome space, the so-called Multidimensional Random Coefficient Multinomial Logit Model, to verify its quality. The initial findings revealed the creation of a construct map consisting of five levels. The researchers determined the cut-off point in the form of the threshold level after considering the Wright Map criteria area for each aspect. Lastly, the measurement model was examined to provide adequate evidence of the internal structure's validity and reliability. In conclusion, students' skill levels can be measured accurately using multidimensional assessments, even though the levels of mathematical capabilities of the students varied from low to moderate to high. Therefore, it provides significant evidence of the mathematical skill measurement model to diagnose seventh-grade students' learning. The significant implications contributed to educational measurement and evaluation are that machine learning algorithms can provide more accurate and consistent scoring of assessments compared to human graders. With accurate assessment using machine learning, teachers can gain deeper insights into individual students' mathematical skills across multiple dimensions.